2015
DOI: 10.1016/j.paid.2015.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Introversion and human-contaminant disgust sensitivity predict personal space

Abstract: How far do people prefer to stand from others during interpersonal interactions? Individuals vary in what has been termed personal space, and this variation appears to be systematic. For instance, personal space tends to be larger among more introverted individuals. The present study investigated whether personality variables relevant to threat perceptions may predict personal space. One type of threat that may be neutralized via physical distancing is infectious disease. This study examined whether individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…But we predict that wariness of people in general is a core output of the behavioral immune system and argue that this ought to be the first-order prediction about how pathogen avoidance motivations influence social cognition. To our knowledge, only one study has investigated a corollary hypothesis and identified a positive correlation among humans between individual differences in disgust sensitivity and the need for larger personal spaces in interpersonal interactions (Park, 2015 ). This interesting finding is aligned with the argument advanced here but leaves unexamined whether high pathogen avoidance motivation not only motivates people to avoid interactions with outgroups but prompts them to avoid others in general.…”
Section: Introductionmentioning
confidence: 99%
“…But we predict that wariness of people in general is a core output of the behavioral immune system and argue that this ought to be the first-order prediction about how pathogen avoidance motivations influence social cognition. To our knowledge, only one study has investigated a corollary hypothesis and identified a positive correlation among humans between individual differences in disgust sensitivity and the need for larger personal spaces in interpersonal interactions (Park, 2015 ). This interesting finding is aligned with the argument advanced here but leaves unexamined whether high pathogen avoidance motivation not only motivates people to avoid interactions with outgroups but prompts them to avoid others in general.…”
Section: Introductionmentioning
confidence: 99%
“…Auditory and tactile senses are also impacted by behavioral immune responses: Visual disease primes increase tactile sensitivity, and lead to perceptions of individuals with foreign accents as more distant, especially for participants scoring higher in disgust sensitivity (Reid et al, 2012; Hunt et al, 2017). Human-specific disgust sensitivity also predicts people’s preferred amount of personal space (Park, 2015).…”
Section: Physiological Foundations Of the Behavioral Immune Systemmentioning
confidence: 99%
“…In the second study, we used the stop-distance task with a higher ecological validity. The chosen distance to the approaching experimenter was on average 1.05 m. Thus, PS sizes determined by means of the bubble task and the stop-distance task were very similar, but considerably higher than the preferred distance by adults (M ¼ 0.42 m) as reported by Park (2015). Since PS size is correlated with the status, authority, and age of the approaching person, this finding seems plausible.…”
Section: Discussionmentioning
confidence: 71%